2002
DOI: 10.1046/j.0962-1075.2001.00301.x
|View full text |Cite
|
Sign up to set email alerts
|

Germ‐line transformation of the Australian sheep blowfly Lucilia cuprina

Abstract: The Australian sheep blowfly, Lucilia cuprina, is the most important economic insect pest for the sheep industries in Australia and New Zealand. piggyBac-mediated germ-line transformation of L. cuprina was achieved with a helper plasmid that had the Drosophila melanogaster hsp70 promoter controlling expression of the transposase and a piggyBac vector with an EGFP marker gene. Two transformant lines were obtained, at a frequency of approximately 1-2% per fertile G0. One of these lines has a single copy of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 43 publications
(78 reference statements)
0
36
0
Order By: Relevance
“…In L. cuprina embryos, the use of the polyubiquitin promoter resulted in the transient expression of EGFP in 40% of injected embryos, whereas neither the hr5-ie1 nor actin5C promoters resulted in observable EGFP expression (Heinrich et al, 2002). The transformed Caribbean fruit fly, A. suspensa, has been marked with polyubiquitin-regulated Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In L. cuprina embryos, the use of the polyubiquitin promoter resulted in the transient expression of EGFP in 40% of injected embryos, whereas neither the hr5-ie1 nor actin5C promoters resulted in observable EGFP expression (Heinrich et al, 2002). The transformed Caribbean fruit fly, A. suspensa, has been marked with polyubiquitin-regulated Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We found that both piggyBac and Minos can transpose in blowfly embryos (Heinrich et al, 2002). The most effective helpers in these assays were hsp70-piggyBac (with heat shock) and Minos RNA.…”
Section: Interplasmid Transposition Assaysmentioning
confidence: 90%
“…Two transformant lines were obtained with the hsp70-piggyBac helper and have now been maintained for 14 generations (Heinrich et al, 2002). Both were obtained from a single G 0 male.…”
Section: Germline Transformation Of L Cuprinamentioning
confidence: 99%
“…Transformed species that may be controlled by SIT or CLR programs include medfly (Handler et al, 1998), caribfly (Handler and Harrell, 2001a), Oriental fruit fly (Handler and McCombs, 2000), pink bollworm (Peloquin et al, 2000), sheep blowfly (Heinrich et al, 2002), and Anopheles albimanus (Perera et al, in press), among several others. piggyBac was originally discovered as the causative agent of few polyhedra (FP) mutations in baculoviruses passed through the Trichoplusia ni TN-368 cell line (Fraser et al, 1983;Cary et al, 1989).…”
Section: Piggybacmentioning
confidence: 99%